Colonialism, Culture, Whales The Cetacean Quartet - Huggan, Graham (Environmental Cultures, 2018)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Colonialism, Culture, Whales: The Cetacean Quartet explores how our attitudes to whales, whale hunting, and whale watching expose colonial attitudes to the natural world in modern Western culture. Foraging across the disciplines and moving between ideas and methods drawn from postcolonial criticism, animal studies, and environmental humanities, the book critically examines the colonial histories of whaling, their legacies in contemporary tourism from whale-watching excursions to the performing orcas at SeaWorld, and cultural representations of anxieties about extinction in recent literature, television, and film. Extensively researched and engagingly written, the four essays that comprise The Cetacean Quartet should appeal to scholars in a number of different fields as well as to general readers interested in finding out more about our enduring, guilt-ridden fascination with one of the world's most iconic living creatures, the whale.